Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review: 61

Answer

The solution is $\frac{1}{3}$.

Work Step by Step

(3x-1)(9$x^{2}$+3x+1)=0 (3x-1) =0 or (9$x^{2}$+3x+1)=0 3x-1+1=0+1 or (9$x^{2}$+3x+1)=0 3x=1 or no solution x=$\frac{1}{3}$ The solution is $\frac{1}{3}$. Check Let x= $\frac{1}{3}$ (3x-1)(9$x^{2}$+3x+1)=0 (3*$\frac{1}{3}$-1)(9*$(1/3)^{2}$+3*1/3+1)=0 (1-1)(9*$(1/3)^{2}$+3*1/3+1)=0 0*(9*$(1/3)^{2}$+3*1/3+1)=0 0=0
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.